Pengetahuan dan Sikap Kader Posbindu terhadap Penyakit DM dan TB paru di Kota Manado - Mokoginta, Karlina Renata; Palandeng, Henry M.F. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2016)
Diabetes mellitus is a metabolic disease with characteristic hyperglycemia. Indonesia is in the 7th place of the most DM patients in the world (7,4 million patients) in 2012. Pulmonary tuberculosis is a chronic infectious disease caused by the infectious mycobacterium tuberculosis. Indonesia has the 5th most cases in the world (520.000 cases) in 2013. Posbindu as a heath program that is close to the community for prevention and detection of disease. This study aims to describe the knowledge and attitude of posbindu cadres about diabetes mellitus and pulmonary tuberculosis in Manado city. This study is a research using cross sectional descriptive. The population in this study was 28 posbindu in Manado city, which each posbindu has 5 members. The samples were choosen with purposive sampling method. The sample is 30 Posbindu members. The result of this study was taking using questionnaire. This study is doing on November 2105-January 2016. The result showed that all cadres get score above the standard in knowledge and attitude about diabetes mellitus and pulmonary tuberculosis in Manado city. Both well knowledge and attitude are the results of routine socialization by doctors and health workers to the cadres.